Effects of BIS-MEP on Reversing Amyloid Plaque Deposition and Spatial Learning and Memory Impairments in a Mouse Model of β-Amyloid Peptide- and Ibotenic Acid-Induced Alzheimer’s Disease - Wang, Yu; Xia, Jia; Shen, Mengjun; Zhou, Yifan; Wu, Zhe; Shi, Yuhuan; Xu, Jianrong; Hou, Lina; Zhang, Rui; Qiu, Zhuibai; Xie, Qiong; Chen, Hongzhuan; et al. (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease (AD) is the main type of dementia and is characterized by progressive memory loss and a notable decrease in cholinergic neuron activity. As classic drugs currently used in the clinic, acetylcholinesterase inhibitors (AChEIs) restore acetylcholine levels and relieve the symptoms of AD, but are insufficient at delaying the onset of AD. Based on the multi-target-directed ligand (MTDL) strategy, bis-(-)-nor-meptazinol (BIS-MEP) was developed as a multi-target AChEI that mainly targets acetylcholinesterase catalysis and the β-amyloid (Aβ) aggregation process. In this study, we bilaterally injected Aβ oligomers and ibotenic acid (IBO) into the hippocampus of ICR mice and then subcutaneously injected mice with BIS-MEP to investigate its therapeutic effects and underlying mechanisms. According to the results from the Morris water maze test, BIS-MEP significantly improved the spatial learning and memory impairments in AD model mice. Compared with the vehicle control, the BIS-MEP treatment obviously inhibited the acetylcholinesterase activity in the mouse brain, consistent with the findings from the behavioural tests. The BIS-MEP treatment also significantly reduced the Aβ plaque area in both the hippocampus and cortex, suggesting that BIS-MEP represents a direct intervention for AD pathology. Additionally, the immunohistochemistry and ELISA results revealed that microglia (ionized calcium-binding adapter molecule 1, IBA1) and astrocyte (glial ﬁbrillary acidic protein, GFAP) activation and the secretion of relevant inflammatory factors (TNF and IL-6) induced by Aβ were decreased by the BIS-MEP treatment. Furthermore, BIS-MEP showed more advantages than donepezil (an approved AChEI) as an Aβ intervention. Based on our findings, BIS-MEP improved spatial learning and memory deficits in AD mice by regulating acetylcholinesterase activity, Aβ deposition and the inflammatory response in the brain.